2006
DOI: 10.17221/3744-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of storage diseases on apples of selected cultivars and advanced selections grown with and without fungicide treatments

Abstract: ABstrAct:In the course of a 3-year study the natural occurrence of storage diseases in ambient air storage with 1 to 2°C was evaluated on samples of 30 cultivars and advanced selections that were harvested from orchards with and without the use of fungicide treatments. Based upon the frequency of occurrence, bitter rot and grey mould were the most common diseases in this study followed by blue mould and brown rot. Fungicide treatments applied in the orchard with integrated plant protection reduced total fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Similar observations were also seen on occurrence of storage rot on apples obtained from comparable conditions in other studies (Deel and Prange, 1993). Blazek et al (2006) further reported that fruits of very susceptible cultivar were destroyed by rotting after 100 days storage. Kaul (1984) also found that most of the commercial apple cultivars were susceptible to rot causing fungal pathogens.…”
Section: Resultsmentioning
confidence: 97%
“…Similar observations were also seen on occurrence of storage rot on apples obtained from comparable conditions in other studies (Deel and Prange, 1993). Blazek et al (2006) further reported that fruits of very susceptible cultivar were destroyed by rotting after 100 days storage. Kaul (1984) also found that most of the commercial apple cultivars were susceptible to rot causing fungal pathogens.…”
Section: Resultsmentioning
confidence: 97%
“…Fungal succession in apples probably starts anew after each fungicide application and therefore endophytic fungi and fungi causing postharvest diseases occur in organically produced apples more frequently than in apples from integrated production. Blažek et al (2006) recorded symptoms of bitter rot (Neofabraea) and grey mould (Botrytis cinerea; together 32.48% and 14.74% of apples without chemical protection and with chemical protection, respectively) more frequently than those of brown rot (Monilinia fructigena; 1.57% and 0.3%) and blue mould (Penicillium; 5.56% and 2.00%). Ivić et al (2012) found the species Monilinia fructigena (0-7.03% of apples per year), Penicillium expansum (0.1-0.53%), Botrytis cinerea (0.2-0.53%) in apples of cultivar Idared (stored in a storage room without temperature regulation), but Neofabraea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of different production systems Blažek et al (2006) compared frequencies of occurrence of bitter rot (Neofabraea vagabunda -formerly N. alba or N. malicorticis), grey mould (Botrytis cinerea), brown rot (Monilinia fructigena) and blue mould (Penicillium expansum) of 30 apple cultivars in an orchard without chemical protection (= organic production system) and in an orchard with chemical protection (= integrated production system or chemical production system). They found lower frequencies of occurrence of the fungal postharvest disease on apples from trees with chemical protection than from those without chemical protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations